2016
DOI: 10.1111/ele.12559
|View full text |Cite
|
Sign up to set email alerts
|

Climate determines vascular traits in the ecologically diverse genus Eucalyptus

Abstract: Current theory presumes that natural selection on vascular traits is controlled by a trade-off between efficiency and safety of hydraulic architecture. Hence, traits linked to efficiency, such as vessel diameter, should show biogeographic patterns; but critical tests of these predictions are rare, largely owing to confounding effects of environment, tree size and phylogeny. Using wood sampled from a phylogenetically constrained set of 28 Eucalyptus species, collected from a wide gradient of aridity across Aust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
124
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 158 publications
(141 citation statements)
references
References 44 publications
13
124
1
3
Order By: Relevance
“…In the present study, when analyzing stem density, anatomy and theoretical Ks, a general trade-off did arise between wood density and Ks, which is in agreement with results reported by Pfautsch et al (2016) for Eucalyptus growing in Australia. However, as in the case of Eucalyptus branches (Barotto et al, 2016), this should not necessarily imply a trade-off between hydraulic efficiency and safety.…”
Section: Possible Ecological Implications Of the Stem Wood Anatomy Ofsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, when analyzing stem density, anatomy and theoretical Ks, a general trade-off did arise between wood density and Ks, which is in agreement with results reported by Pfautsch et al (2016) for Eucalyptus growing in Australia. However, as in the case of Eucalyptus branches (Barotto et al, 2016), this should not necessarily imply a trade-off between hydraulic efficiency and safety.…”
Section: Possible Ecological Implications Of the Stem Wood Anatomy Ofsupporting
confidence: 92%
“…However, studies using different approaches have suggested that Eucalyptus wood structure (anatomy and density of branches) is associated with functional traits involved in stress tolerance or avoidance (e.g. Monteoliva et al, 2015;Barotto et al, 2016), and that it determines the distribution patterns of different species in an aridity stress gradient (Pfautsch et al, 2016). Analysis relating branch anatomy and function in three Eucalyptus species showed that vessel diameter distribution is a key trait correlated not only with measured maximum Ks, but also with the species vulnerability to cavitation (Barotto et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The influence of pathlength and age occur in tandem and both effects follow power functions, albeit they may not follow universal scaling exponents [63]. In addition, conduit diameters usually also widen with increasing water availability (i.e., environmental effect) as recently demonstrated for herbaceous [64] and woody species [56].…”
Section: Conduit Tapermentioning
confidence: 93%
“…Besides immediate responses to water availability, trees can adjust their hydraulic system in response to long-term availability of water [20,56]. Selection processes have resulted in specialization of anatomical structures involved in water transport within species and along environmental gradients.…”
Section: Specialized Wood Anatomymentioning
confidence: 99%
See 1 more Smart Citation